Self-setting Calcium Phosphate Enhanced with Osteoconduction and Bioactivity for Bone Cement - Sirirat Tubsungnoen Rattanachan (Science Faculty of Chiang Mai University, 2019)
Calcium phosphate cements (CPC) have been widely applied as bone repair materials, biodegradable biomaterials or tissue engineering scaffolds. CPC can set and harden in the body at low temperature, but their use has been restricted due to their low biodegradable rate and osteoconductivity. The aim of this work was to study the effects of b-tricalcium phosphate (b-TCP; b-Ca3(PO4)2) and chitosan content on the properties of the CPC. b-TCP was mixed into the apatite-based cement with concentrations up to 40 % (w/w) to form the so-called composite biphasic calcium phosphate cements (BCPC). The compressive strength, bioactivity, degradation and cytotoxicity of the samples were evaluated after soaking in a simulated body fluid (SBF) at 37 °C for 7 days. The degradation rate was found to be higher in cement containing increasing b-TCP concentrations. Apatite formation with oriented plate-like morphology was denser on the BCPC surface after soaking in SBF for 7 days. This BCPC could be considered as a highly biodegradable and bioactive bone cement compared to the apatite CPC. This new self-setting calcium phosphate cement containing 20 % (w/w) b-TCP formed a mixture of HA:b-TCP at a ratio of 60:20 after setting and was found to be a good candidate for bone cement applications.